COLLABORATION IN BUILDING AND PRESERVING A HEALTHY ENVIRONMENT TO CREATE A BRIGHT GENERATION OF SOCIETY (CASE STUDY OF BONEOGE VILLAGE, LAKUDO DISTRICT, CENTRAL BUTON REGENCY) - Agusalim, Agusalim; Suryanti, Suryanti; Muhammad Yusnan; Farisatma; Waode Riniati; Hasim (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to describe and analyze the forms of community collaboration in building and preserving a healthy environment in Boneoge Village, Lakudo District, Central Buton Regency. This study uses a qualitative approach with descriptive methods to deeply understand community participation in environmental conservation activities. Data collection techniques were carried out through field observations, interviews with community leaders and residents, and documentation of community activities. The results of the study indicate that collaboration between the community, local leaders, and various related parties plays a significant role in increasing public awareness of the importance of maintaining environmental cleanliness and sustainability. Social activities such as community service, waste management, and environmental outreach can encourage the formation of collective community participation in maintaining a clean and healthy environment. In addition to having an impact on environmental conditions, these activities also strengthen social solidarity and public awareness in supporting sustainable environmental development.